The Technology-Enhanced Teaching Reading of English in Junior High School Level: Teachers Perspectives - Rachmawati, Umi; Manggolo, Noor Sahid Kusuma Hadi; Prananda, Alivia Revan (Universitas PGRI Semarang, 2025)
Junior high school reading instruction has been used extensively to help meet the objectives of the national curriculum. Teachers and students are encouraged to conduct more advanced technological classrooms by the use of digital technology that has evolved into artificial intelligence. The purpose of this case study was to determine the state of reading instruction at the junior high school level using digital technologies. This study covers the opportunities and challenges for the teachers and students to deal with digital technology and artificial intelligence in the reading class. The data were gathered through observation and interview with the teachers and the students. The results of this study share that (1) it is challenging for the English teacher to use digital technology in the teaching reading, (2) digital technology offers multimodality that help the student to get better understanding on their reading, (3) the integration of artificial intelligence is discussed to get better formula of its implementation, (4) artificial intelligence may support the teachers teaching preparation, and several other challenges are highlighted in details.